THE EFFECTIVENESS OF USING SIWAK TOOTHPASTE ON PLAQUE ACCUMULATION IN FIXED ORTHODONTIC APPLIANCES USERS’ - HALIM, HIMAWAN; AYULIA SALSABILA, TALITHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to determine the ability of toothpaste containing Salvadora persica (Siwak) to reduce the accumulation of dirt in the oral cavity compared to ordinary toothpaste users in fixed orthodontic users. Methods: It was conducted on 40 subjects, divided into two groups of A and B. Group A uses Siwak, while Group B uses ordinary toothpaste. The research subjects were students that utilized fixed appliances for at least 6 months and without periodontal disease. Data were obtained by measuring the plaque level before and after using the toothpaste. Results: A significant relationship between the use of Siwak and ordinary toothpaste by reducing its accumulation in patients using fixed orthodontic appliances and a Chi-square statistical test value of 0.018. Conclusion: The use of Siwak is more effective in reducing plaque accumulation in fixed orthodontic appliance users compared to ordinary toothpaste.